Biodegradation of screenings from sewage treatment by white rot fungi - Anna Civzele; Alise Anna Stipniece-Jekimova; Linda Mezule (Fungal Biology and Biotechnology)
Abstract Wastewater treatment plants (WWTPs), particularly activated sludge systems, generate significant amounts of various types of waste, including screenings, primary sludge, and secondary sludge. While substantial research has been conducted on the recovery and valorization of sewage sludge, the treatment and utilization of screenings remain underexplored. In response, this study investigates the potential of white rot fungi to degrade cellulose-containing waste screened during the preliminary treatment and examines the production patterns of lignocellulolytic enzymes in the presence of this waste. The studied fungi exhibited variable enzymatic responses depending on the type of substrate, however, their adaptability highlighted the potential in fungal-mediated bioconversion processes. P. dryinus and T. versicolor were identified as strong and adaptive candidates for oxidative enzyme production, with P. dryinus showing laccase activity up to 1691.75 ± 12.22 U/mg and degrading 44.46% of carbohydrates in tested screenings. I. lacteus and B. adusta were predominantly observed in cellulolytic enzyme production, with B. adusta ensuring a 43.49% reduction in carbohydrate content of screenings. As a result of fungal cultivation in WWTP waste, the production potential of 34 to 46 kg of sugars per ton of screenings was determined. Therefore, the study presents a promising approach for the sustainable treatment of screenings and the development of waste management and resource recovery strategies for WWTP-derived waste.